Sistem Pakar Identifikasi Ras Kucing Menggunakan Metode Forward Chaining - Bagus Riandi; Fajar Ratnawati; Eva Yumami (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Cat breed identification is a complex process and requires an in-depth understanding of the physical and genetic characteristics of cats. In this study, a forward chaining method to identify cat breeds based on their morphological features. The forward chaining approach allows us to make logical and systematic inferences from the given facts. In this method, rules are built based on the common physical characteristics associated with each cat breed. These rules are then used to perform inference based on the given facts. This process is done iteratively until no additional rules can be applied. The results of this study show that the forward chaining method is effective in identifying cat breeds. By using the right features, cat breed identification has a high success rate. This method can be used as a tool for animal experts or cat lovers in recognizing cat breeds more accurately.